Analisis Dispensasi Kawin Karena Hamil Perspektif Maslahah Mursalah (Studi Penetapan Pengadilan Agama Tais) - Yanti, Revi; Yunus, Fatimah; Julir, Nenan (UIN Fatmawati Sukarno Bengkulu, 2024)
Abstract: Law Number 16 of 2019 article 7 aims to ensure that prospective husbands and wives are ready in body and soul to realize the goal of a good marriage without ending in divorce and to have healthy and quality offspring. This type of research is a type of field research using a qualitative descriptive approach. The results of the research show that the judge's considerations are seen from the first side, considering the reasons for applying for a Marriage Dispensation, secondly considering the evidence at the trial which consists of written evidence and witnesses, finally legal considerations which include positive law and Islamic law, where the judge looks at on the aspects of harm and benefit that will be obtained. There are three aspects to reviewing the benefits of Murlah. The first aspect of the problem is the aspect of child protection, the second aspect is preventing unregistered marriages and the third is to maintain honor, while from the mafsadat aspect, namely the maintenance of religion is not achieved (hifzh al-din), there has been a violation of Islamic law regarding the prohibition of adultery. When two things come together between problemat and madharat then it must be returned to the original rule, namely